До життєпису Костя Широцького (липень 1918 – вересень 1919 рр.) - Горбатюк, В.; Забашта, Р. (Студії мистецтвознавчі, 2009)
The reader is introduced to the archive documents dealing with the last period of the life of Kost Shyrotskyi (pen name Ladyjenko), (26.05.1886–13.09.1919) – eminent scientist, art, literature and folklore researcher, archeologist, active member of the renaissance movement in Ukrainian culture, schooling and sciences, author of more then 150 works. The proposed materials belong to the State Kamianets-Podilskyi University archive and represent a part of Kchmelnytskyi State Region Archive. The document’s chronology (about 20 in number) is limited by the 10-th of July and the 20-th of September, so it is the period of 14 months. They consists of Kost Shyrotskyi letters to Ivan Ogienko, professor and rector of just organized (October, 22) Kamianets-Podilskyi University, his autobiography (Curriculum vitae) and other documents. They include much information about concrete facts of Sherotskyi’s life. At the same time they introduce the reader to the atmosphere and problems of this difficult time, reveal the personal features of the scientist, his eagerness to creative work, his relationships with his colleagues, relatives and representatives of the national movement at the beginning of the 20-th century. We clearly can guess all the tragedy of this remarkable Ukrainian, who left this life being not realized.